The Impact of Seating Location and Seating Type on Student Performance - Amy Oakes Wren; Felice Williams; John A. Vassar; Karen D. James; Tami L. Knotts; Michael D. Meeks (MDPI AG, 2013)
While an extensive body of research exists regarding the delivery of course knowledge and material, much less attention has been paid to the performance effect of seating position within a classroom. Research findings are mixed as to whether students in the front row of a classroom outperform students in the back row. Another issue that has not been fully examined in higher education is the effect of environmental factors, specifically seating type, on student performance. This study examines the impact of both factors-seating location and seating type-on overall performance. Data were collected over a 10-year period from 1,138 undergraduate senior business students during their capstone course. The findings suggest that student performance is not significantly altered by seating location or seating type.